Analysis of the Effectiveness of Using Contractual Sentences (Sighat) in Islamic Marriages in Indonesia: John Langshaw Austin's Speech Act Theory Perspective - Fauzi, Akhmad (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyse the effectiveness of the use of the marriage contract (sighat) in Islamic marriages in Indonesia, based on John Langshaw Austin's speech act theory. The study used a qualitative method, collecting and analysing data from relevant written sources. The results of the study show that the kalimat akad (sighat) in Islamic marriages in Indonesia is significantly effective in creating marriages that are legally and socially valid. Analysis using Austin's theory of speech acts shows that the marriage contract has a strong performative function, i.e. it can perform the action of marriage and bind the two parties. However, the study also found that there are some challenges in the use of marriage contracts in Islamic marriages in Indonesia, such as a lack of understanding of the meaning and function of marriage contracts among Indonesian Muslim communities. Therefore, this study recommends efforts to increase public awareness and understanding of the meaning and function of the marriage contract (sighat) in Islamic marriages in Indonesia.